Endovascular Aortic Aneurysm and Dissection Repair (EVAR) in Iran: Descriptive Midterm Follow-up Results - Haji Zeinali, Ali Mohammad (Iran J Radiol, 2016)
BACKGROUND: Endovascular repair of aorta in comparison to open surgery has a low early operative mortality rate, but its long-term results are uncertain. OBJECTIVES: The current study describes for the first time our initial four-year experience of elective endovascular aortic repair (EVAR) at Tehran heart center, the first and a major referral heart center in Iran, as a pioneer of EVAR in Iran. PATIENTS AND METHODS: A total of 51 patients (46 men) who had the diagnosis of either an abdominal aortic aneurysm (AAA) (n = 36), thoracic aortic aneurysm (TAA) (n = 7), or thoracic aortic dissection (TAD) (n = 8) who had undergone EVAR by Medtronic stent grafts by our team between December 2006 and June 2009 were reviewed. RESULTS: The rate of in-hospital aneurysm-related deaths in the group with AAA stood at 2.8% (one case), while there was no in-hospital mortality in the other groups. All patients were followed up for 13-18 months. The cumulative death rate in follow-up was nine cases from the total 51 cases (18%), out of which six cases were in the AAA group (four patients due to non-cardiac causes and two patients due to aneurysm-related causes), one case in the TAA group (following a severe hemoptysis), and two cases in the TAD group (following an expansion of dissection from re-entrance). The major event-free survival rate was 80.7% for endovascular repair of AAA, 85.7% for endovascular repair of TAA, and 65.6% for endovascular repair of TAD. CONCLUSION: The endovascular stent-graft repair of the abdominal and thoracic aortic aneurysm and aortic dissection had high technical success rates in tandem with low-rate early mortality and morbidity, short hospital stay, and acceptable mid-term free symptom survival among Iranian patients.